Definitive chemoradiation for locally-advanced oral cavity cancer: A 20-year experience. (May 2018) - Foster, Corey C.; Melotek, James M.; Brisson, Ryan J.; Seiwert, Tanguy Y.; Cohen, Ezra E.W.; Stenson, Kerstin M.; Blair, Elizabeth A.; Portugal, Louis; Gooi, Zhen; Agrawal, Nishant; Vokes, Everett E.; Haraf, Daniel J.
Highlights: Over 20 years, we offered definitive chemoradiation for oral cavity cancer. Oncologic outcomes were encouraging. There was a 10% rate of long-term feeding tube dependency. The rate of osteoradionecrosis requiring surgical intervention was 21%. The risk of osteoradionecrosis was modulated by disease subsite. Abstract: Objectives: Definitive chemoradiation (CRT) for oral cavity squamous cell carcinoma (OC-SCC) is often criticized for poor efficacy or toxicity. We describe a favorable 20-year experience of primary CRT for locally-advanced OC-SCC. Materials and Methods: Patients with locally-advanced, stage III/IV OC-SCC receiving primary concomitant CRT on protocols from 1994 to 2014 were analyzed. Chemotherapy included fluorouracil and hydroxyurea with other third agents. Radiotherapy (RT) was delivered once or twice daily to a maximum dose of 70–75 Gy. Intensity-modulated RT (IMRT) was exclusively used after 2004. Progression-free survival (PFS), overall survival (OS), locoregional control (LRC), and distant control (DC) were calculated by the Kaplan-Meier method and compared across treatment decades using the log-rank test. Rates of osteoradionecrosis (ORN) requiring surgery were compared across treatment decades using the Chi-square test. Results: 140 patients with locally-advanced OC-SCC were treated with definitive CRT. Of these, 75.7% had T3/T4 disease, 68.6% had ≥N2 nodal disease, and 91.4% had stage IV disease. Most common primary sites were oral tongue (47.9%) and floor of mouth (24.3%). Median follow-up was 5.7 years. Five-year OS, PFS, LRC, and DC were 63.2%, 58.7%, 78.6%, and 87.2%, respectively. Rates of ORN and long-term feeding tube dependence were 20.7% and 10.0%, respectively. Differences in LRC ( P = 0.90), DC ( P = 0.24), PFS ( P = 0.38), OS ( P = 0.10), or ORN ( P = 0.38) were not significant across treatment decades. Conclusion: Definitive CRT is a viable and feasible strategy for organ preservation for patients with locally-advanced OC-SCC.